Application of purple basil leaf anthocyanins-loaded alginate-carrageenan emulgel beads in gelatin-based jelly candies - Ozcan, Basak Ebru; Karakas, Canan Yagmur; Karadag, Ayse (ELSEVIER, 2024)
Jelly candies could be considered promising food matrices for the delivery of bioactive compounds such as anthocyanins (ACNs). In this study, gelatin-based jelly candies were fortified with free ACNs-rich purple basil leaf extract (PBLE) and PBLE-loaded emulgel beads. The interaction between free ACNs and gelatin in the jelly matrix resulted in a lower release of ACNs in the mouth (8.27 %) and gastric stage (74.44 %) compared to those of free extract (24.92 and 86.13 %), as well as some protection in the intestinal stage. The release of ACNs from the jellies enriched with PBLE-loaded emulgel beads only began in the intestinal stage and reached 66.34-70.75 % of the initial load. Compared to those of PBLE-loaded emulgel beads, the introduction of beads within the jelly matrix increased the in vitro release of ACNs. The jelly samples enriched with PBLE-loaded emulgel beads yielded higher hardness, adhesiveness, flexibility, and chewiness compared to samples with free PBLE. While the color and appearance of jellies fortified with encapsulated PBLE were impaired, they got the highest sensory acceptance scores due to the masking of the bitter taste of the free extract. ACNs-loaded emulgel beads could be a viable method for fortifying jelly candies.
Keywords: In vitro digestion; Encapsulation; Sodium alginate; Carrageenan; Ionic gelation; Double emulsion; STABILITY; TEXTURE; MICROENCAPSULATION; OPTIMIZATION; CURCUMIN; RELEASE; Biochemistry & Molecular Biology; Chemistry; Polymer Science